2019
DOI: 10.1111/jphd.12304
|View full text |Cite
|
Sign up to set email alerts
|

Dental care utilization: patterns and predictors in persons living with HIV in British Columbia, Canada

Abstract: Objectives To identify the predisposing, enabling, and need factors of the Andersen and Newman (A&N) model and their associations with the pattern of dental service utilization in a sample of people living with HIV (PLHIV) in British Columbia. Methods Participants responded anonymously to a 40‐item online questionnaire to explore the patterns of dental service utilization. Following the descriptive statistics, the associations between A&N model factors and main outcome variables (having a dental visit in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 20 publications
8
20
0
Order By: Relevance
“…We utilized the A&N model of health service utilization to identify the strongest predictors of self-reported oral health and dental service utilization as employed in our previous studies. [31,32,33] For predisposing factors, we found that adolescents who reported receiving some oral health education were more likely to have visited a dental professional within the last year, which corroborates the ndings from Jessani et al in 2016, and Jessani et al in 2019. [32,31] However, 80% of adolescents had not been exposed to any form of oral health education.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We utilized the A&N model of health service utilization to identify the strongest predictors of self-reported oral health and dental service utilization as employed in our previous studies. [31,32,33] For predisposing factors, we found that adolescents who reported receiving some oral health education were more likely to have visited a dental professional within the last year, which corroborates the ndings from Jessani et al in 2016, and Jessani et al in 2019. [32,31] However, 80% of adolescents had not been exposed to any form of oral health education.…”
Section: Discussionsupporting
confidence: 88%
“…[31,32,33] For predisposing factors, we found that adolescents who reported receiving some oral health education were more likely to have visited a dental professional within the last year, which corroborates the ndings from Jessani et al in 2016, and Jessani et al in 2019. [32,31] However, 80% of adolescents had not been exposed to any form of oral health education. This is concerning as adolescents are in a developmental stage during which they establish lifelong habits, attitudes, and beliefs.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations